"Testament" Macieja Byldy z Nowego Kramska. Uzupełnienie do Księgi ławniczej Nowego Kramska = "Testament" by Maciej Bylda of Nowe Kramsko. Supplement to the Liber Actorum Civilium [Lay Jury Book] of Nowe Kramsko - Benyskiewicz, Krzysztof (1959- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Article "Testament" by Maciej Bylda of Nowe Kramsko. Supplement to the Liber Actorum Civilium [Lay Jury Book] of Nowe Kramsko deals with the land grant made in 1697 to the benefit of the church in Nowe Kramsko by the local landowner Maciej Kitkow Bylda. The document confirming the grant was originally placed in the Liber Actorum Civilium [Lay Jury Book] of Nowe Kramsko.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia